Algebraic operations of the univalent functions with regard to class S - Prabhu, R.Ambrose; Bhaskaran, S. (International Journal of Psychosocial Rehabilitation, 2020)
In this article, the authors expressed their results on algebraic sum of two functions from class ? of normalized univalent function defined in the open unit disc ?:?: |?| < 1, is not univalent, and need not be in ?.